Electrodeposition of a CoNiCu medium-entropy alloy in a water-in-oil emulsion - Yuki Murakami; Yuki Maeda; Atsushi Kitada; Kuniaki Murase; Kazuhiro Fukami (Electrochemistry Communications, 2021)
A medium-entropy alloy (MEA) of CoNiCu with a face-centered cubic structure was successfully obtained by electrochemical deposition. To achieve a nearly equiatomic composition, a water-in-oil emulsion was used as the solution for electrodeposition. Since the water droplets in the emulsion tended to be destroyed within 10 min under electrolysis, the emulsion was periodically irradiated ultrasonically to maintain its emulsified state in order to obtain a continuous film by electrodeposition. Characterization of the film deposited under a constant potential reveals that the deposit is metallic with a face-centered cubic structure. The nearly equiatomic composition suggests that the deposit is a CoNiCu medium-entropy alloy.